2020
DOI: 10.1186/s12943-020-01234-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in tumor microenvironment: new mechanisms, potential therapeutic strategies and future prospects

Abstract: Regulatory T cells (Tregs) characterized by the expression of the master transcription factor forkhead box protein p3 (Foxp3) suppress anticancer immunity, thereby hindering protective immunosurveillance of tumours and hampering effective antitumour immune responses in tumour-bearing hosts, constitute a current research hotspot in the field. However, Tregs are also essential for the maintenance of the immune tolerance of the body and share many molecular signalling pathways with conventional T cells, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
366
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(449 citation statements)
references
References 203 publications
4
366
0
4
Order By: Relevance
“…It has been shown that regulatory T cells play a crucial role in regulating the homeostasis of the immune system and maintaining tolerance [ 130 ]. Moreover, Treg have been found to limit the anti-tumor immune response.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that regulatory T cells play a crucial role in regulating the homeostasis of the immune system and maintaining tolerance [ 130 ]. Moreover, Treg have been found to limit the anti-tumor immune response.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Treg are defined as a T helper cell subpopulation characterized by the co-expression of CD4, CD25, and in large parts of FoxP3, which inhibit the activation and differentiation of CD4 + and CD8 + T cells, subsequently impairing reactivity against autologous and tumor-expressed antigens [ 130 , 133 , 134 ]. According to their biological properties, Treg are generally divided into two groups: natural (n) regulatory T cells and induced (i) regulatory T cells, which commonly express FoxP3 [ 135 ].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…IL-35 and IL-10 promote T cell exhaustion. Metabolic competition for the consumption of IL-2 through the expression of CD25 on Tregs also suppresses T c effector functions [ 33 ]. Tregs are also found in peripheral circulation, but their precise role in facilitating immune evasion are not as well characterized as with the TME-associated Tregs [ 32 ].…”
Section: Mechanisms Of T Cell Senescence Inductionmentioning
confidence: 99%
“…Other immune cells within the TME might also indirectly impact T c senescence. Treg and MDSC populations often support each other’s expansion through positive feedback loops involving TGF-β and other cytokines [ 33 ]. In turn, MDSCs can be expanded by many of the SASP cytokines secreted by T c senescent cells such as TGF-β, IL-6 and IFN-γ [ 39 ].…”
Section: Mechanisms Of T Cell Senescence Inductionmentioning
confidence: 99%
“…Tregs and MDSCs are key regulators of antitumor responses in BLCA, and the intra-tumoral presence of those are correlated with the poor clinical outcome has already been established[30,31]. Tregs serve as a vital immunosuppressive factor to promote tumor occurrence and development, inhibit antitumor immunity, and help in tumor immune escape[32]. Likewise, MDSCs are widely distributed and have strong immunosuppressive activity in the TME that inhibit cytotoxic T cells' proliferation and activation, leading to the failure of the antitumor immune response and promoting cancer progression and chemoresistance[33].…”
mentioning
confidence: 99%